ANALISIS PENGARUH SEKTOR PARIWISATA TERHADAP PENDAPATAN ASLI DAERAH (PAD) 38 KABUPATEN/KOTA DI PROVINSI JAWA TIMUR TAHUN 2018-2023 - Adhellya Putri Suwasono; Nenik Woyanti (Universitas Darul Ulum Islamic Centre Sudirman GUPPI, 2026)
Local Own-Source Revenue (PAD) is an important indicator of regional fiscal independence. PAD in East Java Province remains moderate compared to other provinces on Java Island and shows fluctuating growth, indicating that fiscal capacity is not yet optimal and dependence on central transfers still exists. Meanwhile, the tourism sector has strong potential to increase PAD through tourist arrivals, tourist attractions, hotels, and restaurants. This study aims to analyze the effect of these variables on PAD in East Java Province. This study uses a quantitative approach with panel data from regencies/cities in East Java Province during 2018–2023. Panel data regression is applied to examine the relationship between independent variables and PAD as the dependent variable. The t-test is used to measure partial effects, while the F-test is used to test simultaneous effects. The results indicate that simultaneously, the number of tourists, tourist attractions, hotels, and restaurants significantly affect PAD. Partially, the number of tourists and hotels have a positive and significant effect on PAD, while tourist attractions and restaurants have no significant effect. These findings show that not all tourism indicators directly contribute to PAD, so better tourism management is needed to optimize regional revenue.Keywords: Local Own-Source Revenue, Tourists, Tourist Attractions, Hotels, Restaurants.